The legal nature of the principle of openness in criminal proceedings (Journal of actual problems of jurisprudence, 2019)
The article examines the legal nature of the principle of transparency as a fundamental guideline and start the criminal process of the Republic of Kazakhstan. Actualized the need for further improvement of the legislation defining the basic elements of a mechanism for implementing public. The questions of the need to identify ways to increase openness in criminal proceedings.Key words: the principle of transparency, prosecuting function accusations protection function, the administration of justice.